EFEKTIVITAS SISTEM INFORMASI AKUNTANSI PADA PERUSAHAAN JASA KEUANGAN DI JAKARTA - Dewi Sarina Pakpahan; Afrizon Afrizon (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2020)
The development of accounting information systems in the financial sector is an important topic, especially the development of financial information technology. This study aims to analyze the effect of user competence, organizational culture and top management support on the effectiveness of accounting information systems in financial sector companies. This research method uses survey techniques with a population of financial service organizations. From 30 data collected, multiple regression analysis is used to process the data. Based on the results of tests conducted note that user competency and top management support affect the effectiveness of accounting information systems while organizational culture does not affect the effectiveness of accounting information systems